2021
DOI: 10.1002/advs.202100472
|View full text |Cite
|
Sign up to set email alerts
|

A Photovoltaic Self‐Powered Gas Sensor Based on All‐Dry Transferred MoS2/GaSe Heterojunction for ppb‐Level NO2 Sensing at Room Temperature

Abstract: Traditional gas sensors are facing the challenge of low power consumption for future application in smart phones and wireless sensor platforms. To solve this problem, self-powered gas sensors are rapidly developed in recent years. However, all reported self-powered gas sensors are suffering from high limit of detection (LOD) toward NO 2 gas. In this work, a photovoltaic self-powered NO 2 gas sensor based on n-MoS 2 /p-GaSe heterojunction is successfully prepared by mechanical exfoliation and all-dry transfer m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(50 citation statements)
references
References 56 publications
0
48
0
Order By: Relevance
“…The photoexcited electrons generated in Au can overcome the blocking and injection of conduction band in ZnO, making more free electrons can participate in the chemical reaction with the surface adsorbed O 2 and NO 2 molecules. Niu et al prepared vertically stacked MoS 2 /GaSe heterojunction by all-dry transfer method (Niu et al, 2021). When the p-n junction between MoS 2 and GaSe is exposed to visible light, electronhole pairs in both MoS 2 and GaSe layers are generated by light and tend to migrate at the interface.…”
Section: Sensing Mechanism Of Light-assisted Gas Sensormentioning
confidence: 99%
“…The photoexcited electrons generated in Au can overcome the blocking and injection of conduction band in ZnO, making more free electrons can participate in the chemical reaction with the surface adsorbed O 2 and NO 2 molecules. Niu et al prepared vertically stacked MoS 2 /GaSe heterojunction by all-dry transfer method (Niu et al, 2021). When the p-n junction between MoS 2 and GaSe is exposed to visible light, electronhole pairs in both MoS 2 and GaSe layers are generated by light and tend to migrate at the interface.…”
Section: Sensing Mechanism Of Light-assisted Gas Sensormentioning
confidence: 99%
“…1,2 Therefore, two-dimensional materials have been widely developed for applications like sensing, communication and detection. 3–7 Among multifarious 2D materials, transition metal dichalcogenides (TMDs) have attracted much attention due to their excellent optical and electrical properties. 8 Through flexible hetero-integration, TMDs are stacked into a rich variety of van der Waals heterojunctions (vdWHs) for diverse and outstanding optoelectronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…18 Niu et al reported a self-powered gas sensor based on the MoS 2 /GaSe heterojunction for ppb-level NO 2 sensing at RT. 19 However, the above 2D vdWs heterostructures are mainly exfoliated from their bulk counterparts by various techniques, which possess excellent properties but are not conducive to industrial production. 20 To the best of our knowledge, the fabrication of PdSe 2 /InSe heterostructure via industrial strategies for the room-temperature gas sensing has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%